COFFEE VALUE CHAIN ANALYSIS: A STUDY OF ARAKU AND PADERU REGIONS IN ANDHRA PRADESH - B., Venugopal; Dash, Debendra Nath (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study investigates the factors influencing coffee farmers’ decisions regarding their membership in Farmer Producer Organizations (FPOs) and their selling patterns based on landholding size. Using chi-square tests, the researcher analyses the relationship between income groups and FPO membership and the associations between landholding sizes and the selling channels and buyers for coffee produce. The findings reveal no statistically strong correlation between levels of income and FPO membership, implying that farmers’ actions may be influenced by other variables to join FPOs. In contrast, a robust correlation was found between landholding size and both the market channels utilized for selling produce and the choice of buyers. Smaller farmers typically favored selling to village aggregators and local traders, while larger landholders tended to engage with FPOs and contract buyers. These insights highlight the importance of considering landholding size in understanding market behavior among coffee farmers and encourage further investigation into the underlying factors influencing selling patterns.